Mapping Escolar ( Lepidocybium flavobrunneum ) in Motion: Oceanographic Forces Shaping Its Habitat in the Southwestern South Atlantic, With Insights From Fishers' Perceptions - Lucas Rodrigues; Maria Grazia Pennino; Paul Gerhard Kinas; David Conesa; Alba Fuster‐Alonso; Andrés Domingo; Rodrigo Forselledo; Federico Mas; Bruno Mourato; Rodrigo Sant'Ana; Vinni Santos Thykjaer; Raquel Virginia Marquez Marquez; et al. (Fisheries Oceanography, 2026)
Lepidocybium flavobrunneum [Smith, 1843], commonly known as escolar, is a large pelagic species, important for global and local fisheries, particularly in the southwestern South Atlantic Ocean (SWAO), where it constitutes a significant portion of the catch. However, despite its important socioeconomic role, it remains less studied compared to other large pelagic species. Enhancing research efforts is therefore key to better understanding the ecological processes that influence its spatial and temporal distribution. To address this gap, our study applied species distribution models (SDMs) to escolar's occurrence and abundance using longline fleet data from south Brazil and Uruguay. Estimation and prediction were conducted at the Bayesian framework using the integrated nested Laplace approximation (INLA) methodology combined with the stochastic partial differential equation (SPDE) approach. Our findings reveal a strong correlation between warmer sea surface temperatures and increased escolar occurrence and abundance in the SWAO, particularly during the austral summer, in contrast to cooler‐season patterns observed elsewhere. Escolar's distribution is influenced by the southward and westward movement of seawater driven by the Brazil Current, and its preference for depths greater than 2000 m reflects its oceanic nature. Predicted areas of higher abundance around the continental slope (between 33° and 37° S) and the Rio Grande Rise are linked to the dynamic interaction of warm and cold currents and nutrient‐rich waters. Additionally, escolar's sensitivity to low‐light conditions may explain reduced catches during moonlit nights. A complementary analysis assessing the synergistic influence of sea surface temperature and lunar illumination on escolar occurrence indicated that, under high temperatures (> 22 °C), occurrence is further enhanced during dark nights. Furthermore, semi‐structured interviews with vessel captains revealed that 90% identified temperature (via open‐ended responses) as a key environmental factor driving escolar catches, and 80% of them attributed a strong influence (greater than average catch rates) to temperature, summer season and new moon phase. This study provides new insights into escolar's seasonal and spatial patterns, emphasizing the impact of oceanographic features and light conditions on its distribution. It also highlights the need for further research into the mechanisms driving escolar populations.

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Potential Spatial Mismatches Between Marine Predators and Their Prey in the Southern Hemisphere in Response to Climate Change - Maria Bas; Jazel Ouled‐Cheikh; Alba Fuster‐Alonso; Laura Julià; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Global Change Biology, 2025)
Global change is rapidly reshaping species' habitat suitability ranges, hence leading to significant shifts in the distribution of marine life. Contrasting distributional responses among species can alter the spatial overlap between predators and prey, potentially disrupting trophic interactions and affecting food web dynamics. Here, we evaluate long‐term changes in the spatial overlap of habitat suitability ranges for trophically related species, including crustaceans, fish, penguins, and pinnipeds across 12 Large Marine Ecosystems from the Southern Hemisphere, merged into three primary regions: South America, Southern Africa, Australia and New Zealand. To this aim, we first use Boosted Regression Trees (BRTs) to hindcast and project species‐specific changes in suitable habitat from 1850 to 2100 under two future climate scenarios: SSP1‐2.6 (low climate forcing) and SSP5‐8.5 (high climate forcing). We then analyze changes in species habitat suitability and potential predator–prey spatial overlaps. Findings reveal that marine species generally exhibit changes in their suitable habitats, with pronounced shifts towards higher latitudes under the SSP5‐8.5 scenario. However, contrasting trends emerge among predators across functional groups and regions of South America, Southern Africa, Australia and New Zealand. These variations highlight the need for species and regional‐specific management responses. We also project contrasting spatial mismatches between predators and prey: predators experiencing declines in suitable habitat tend to exhibit greater overlap with their prey in future scenarios, whereas those with expanding suitable habitat show reduced spatial overlap with their prey. This study provides valuable insights that can inform spatial management strategies in response to climate change and illustrate how climate change may weaken species' ability to adapt to climate‐driven environmental changes due to trophic disruptions.

Fish and tips: Historical and projected changes in commercial fish species' habitat suitability in the Southern Hemisphere - Maria Bas; Jazel Ouled-Cheikh; Laura Julià; Alba Fuster-Alonso; David March; Francisco Ramírez; Luis Cardona; Marta Coll (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Water scarcity in central Chile: the effect of climate and land cover changes on hydrologic resources - Ignacio Fuentes; Rodrigo Fuster; David Avilés; Willem Vervoort (Hydrological Sciences Journal, 2021)